Persuasion Knowledge, Alcohol Consumption and Event Sponsorship - Abbaspuli, F.; Jalali, M.; Farhangmehr, M. (Proceedings of the 43rd EMAC Conference - Paradigm Shifts and Interactions, 2014)
This paper examines the impact of event sponsorship by alcohol companies on participants’ perceptions of the events and their intentions to drink. Sponsorship is gaining importance, as companies seek to better communicate with their customers in an increasingly promotion-cluttered environment. When this sponsorship is undertaken by alcohol companies, however, it is not without controversy, particularly for sporting events or those targeted at young people. In a series of experimental studies we show that alcohol sponsorships influence the perceived level of excitement of an event, as well young people’s intentions to drink. This effect can be somewhat mitigated by making persuasion knowledge more salient; however, the association of an alcohol sponsor with an event can be such that the event alone triggers greater drinking intentions.